Konsep Pengendalian Diri Dalam Astangga Yoga Kajian Psikologi - Yus Aditya, I Wayan (Jurnal Yoga dan Kesehatan, 2026)
Self-control is a fundamental ability that allows individuals to regulate their thoughts, emotions, and behaviors to stay in line with their values ​​and long-term goals. In this context, Patanjali’s Ashtanga Yoga offers an eight-step framework that encompasses moral, physical, and spiritual aspects. These eight steps include yama (moral principles), niyama (self-discipline), asana (physical postures), pranayama (breath control), pratyahara (withdrawal from the senses), dharana (concentration), dhyana (meditation), and samadhi (supreme consciousness). This study aims to explore the relevance of Ashtanga Yoga principles in managing emotions, controlling impulses, and improving mental well-being through a modern psychological approach. The literature review shows that Ashtanga Yoga not only teaches practical self-control through meditation, self-discipline, and introspection, but also helps individuals manage stress, improve emotional regulation, and improve life satisfaction. The integration of Ashtanga Yoga principles with modern psychological theories of self-control offers a holistic approach to improving mental well-being. This article makes a scientific contribution by analyzing the potential of Ashtangga Yoga as a framework for the development of better self-control, while proposing its application in contemporary psychological interventions for stress management and improving quality of life.